2006
DOI: 10.1177/1043659606291544
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Seeking Health Care for Acute Coronary Syndromes in a Lebanese Sample

Abstract: Early treatment of patients with acute coronary syndromes (ACS) is crucial to reduce morbidity and mortality. The purpose of this study was to examine delay in seeking care for ACS symptoms in a Lebanese sample and identify predictors of delay. Medical record reviews and interviews using the Response to Symptoms Questionnaire were conducted with 204 ACS patients in coronary care within 72 hours of admission. Median time from symptom onset to hospital arrival was 4.5 hours. Higher education, presence of dyspnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 30 publications
6
49
0
2
Order By: Relevance
“…Median delay was often reported due to distribution skewness resulting from extremely prolonged delay values. While the majority of authors who described the distribution of delay times reported skewness toward longer delay values [16][17][18][19][20][21][22][23][24], McKinley et al [25], who studied treatment seeking behavior among a cohort of Australians and North Americans, reported skewness toward short values.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Median delay was often reported due to distribution skewness resulting from extremely prolonged delay values. While the majority of authors who described the distribution of delay times reported skewness toward longer delay values [16][17][18][19][20][21][22][23][24], McKinley et al [25], who studied treatment seeking behavior among a cohort of Australians and North Americans, reported skewness toward short values.…”
Section: Resultsmentioning
confidence: 97%
“…Of the ones that reported using a conceptual framework, eight [18,21,23,25,[36][37][38][39] have used Leventhal's model [40]. Leventhal's model was used in conjunction with another conceptual framework in three of the studies: Grounded Theory [36], Thematic Framework [37], and Dispositional Optimism [23].…”
Section: Theoretical Framework Utilizedmentioning
confidence: 99%
“…Comparison data from other parts of the world, however, indicate much longer median PHDT such as a median of 195 min in Denmark, observed in a study including 5978 patients [17], 210 min in Greece [27] including 2172 acute coronary syndrome patients and -assessed with substantially smaller sample sizes -of 264 min in South Korea [28]; 270 min in Japan [28] , 271 min in Lebanon [29] and even 384 min in Australia [30].…”
Section: Median Delay Times and Delay Time Windowsmentioning
confidence: 95%
“…The period of pre-hospital delay in the KSA in this study is twice as long as in the UK or USA and is also considerably longer than in other Asian or Middle Eastern countries. 11,17,22,29,41,[56][57][58] Participants' interviews show that transfer delay is the major contributing factor especially for women. However in 2011, the Saudi Project for the Assessment of Coronary Events registry (SPACE), showed a much lower median total pre-hospital delay of 2.5 h (interquartile range: 223 min) for 5055 ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 The CSM was judged to be the most appropriate theoretical framework by which to consider the extensive range of physical and emotional responses that patients experience when coping with STEMI symptoms and to help explain the rationale for these. 8,[25][26][27][28][29][30][31][32][33][34] This study used a non-experimental, survey design, sequentially combining both quantitative and qualitative methods to achieve the study objectives. Explanatory mixed methods are frequently used to gain greater insight into the topic of investigation than that which one method would achieve in isolation.…”
Section: Methodsmentioning
confidence: 99%